Geo Economic Situation of Pakistan in the Light of China Investment - Khan, Muhammad Ijaz; Ijaz, Sonia; Yasmin, Tahira (Annals of Human and Social Sciences, 2023)
This study examines the economic impact of China’s investments within the China-Pakistan Economic Corridor (CPEC) on Pakistan’s geo-economic landscape and investigates the broader geopolitical implications of the China-Pakistan partnership. Data was collected from various sources, including Dr. Ishrat Hussain’s booklet, using purposive sampling. Thematic analysis revealed that while China’s investments, particularly within the China-Pakistan Economic Corridor (CPEC), offer substantial economic opportunities for Pakistan, they also necessitate careful consideration of transparency, debt management, and geopolitical implications to ensure sustainable development and regional stability. In conclusion, this research underscores the intricate interplay between China’s investments, CPEC’s economic impacts, and their geopolitical consequences, emphasizing the need for balanced strategies that harness opportunities while effectively addressing challenges for a resilient and prosperous future. The study’s findings advocate for transparent and sustainable project execution, informed debt management, and diplomatic finesse to optimize the benefits of China’s investments in Pakistan and navigate the evolving geopolitical landscape effectively.